City Wide Participatory Sensing of Air Quality - Rebeiro-Hargrave, Andrew; Fung, Pak Lun; Varjonen, Samu; Huertas, Andres; Sillanpää, Salla; Luoma, Krista; Hussein, Tareq; Petäjä, Tuukka; Timonen, Hilkka; Limo, Jukka; Nousiainen, Ville; Tarkoma, Sasu (Frontiers in Environmental Science, 2021)
Air Pollution is a contributor to approximately one in every nine deaths annually. Air quality monitoring is being carried out extensively in urban environments. Currently, however, city air quality stations are expensive to maintain resulting in sparse coverage and data is not readily available to citizens. This can be resolved by city-wide participatory sensing of air quality fluctuations using low-cost sensors. We introduce new concepts for participatory sensing: a voluntary community-based monitoring data forum for stakeholders to manage air pollution interventions; an automated system (cyber-physical system) for monitoring outdoor air quality and indoor air quality; programmable platform for calibration and generating virtual sensors using data from low-cost sensors and City monitoring stations. To test our concepts, we developed a low-cost sensor to measure particulate matter PM$_{2.5}$, nitrogen dioxide (NO$_{2}$), carbon monoxide (CO), and ozone (O$_{3}$) with GPS. We validated our approach in Helsinki, Finland, with participants carrying the sensor for three months during six data campaigns between 2019 and 2021. We demonstrate good correspondence between the calibrated low-cost sensor data and City’s monitoring station measurements. Data analysis of their personal exposure was made available to the participants and stored as historical data for later use. Combining the location of low cost sensor data with participants public profile, we generate proxy concentrations for black carbon and lung deposition between districts, by age groups and by the weekday. Our contributions to air quality science have applications in epidemiological models and city planning investments.